2023
DOI: 10.1021/acs.jpclett.3c01626
|View full text |Cite
|
Sign up to set email alerts
|

How the Stacking Pattern Influences the Charge Transfer Dynamics of van der Waals Heterostructures: An Answer from a Time-Domain Ab Initio Study

Atish Ghosh,
Biplab Goswami,
Sougata Pal
et al.

Abstract: Here, we perform a time domain density functional study in conjunction with a non-adiabatic molecular dynamics (NAMD) simulation to investigate the charge carrier dynamics in a series of van der Waals heterostructures made of two-dimensional (2D) SnX 2 (X = S or Se)supported ZrS 2 , ZrSe 2 , and ZrSSe monolayers. Results from NAMD simulation reveal delayed electron−hole recombination (in the range of 0.53−2.13 ns) and ultrafast electron/hole transfer processes (electron transfer within 108.3−321.5 fs and hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This method has been used successfully to model photo-excitation dynamics in a wide range of nanoscale and condensed-phase materials, including 3D perovskites with grain boundaries, point defects, dopants, and passivations, perovskites interacting with charge extraction layers, 2D Ruddelsden–Pooper (RP) and Dion–Jacobson (DJ) perovskites, 2D/3D heterostructures, TiO 2 bulk, and two-dimensional materials like black phosphorus, boron nitride, and others. 23,33–37 Earlier photo-induced charge dynamics experiments on 2D DJ perovskites, 2D RP perovskites with edge states and varying numbers of layers, and MAPbI 3 with grain boundaries and localized charges and interfaced with NiO, TiO 2 , and water yielded good findings. 11,33,34,38…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This method has been used successfully to model photo-excitation dynamics in a wide range of nanoscale and condensed-phase materials, including 3D perovskites with grain boundaries, point defects, dopants, and passivations, perovskites interacting with charge extraction layers, 2D Ruddelsden–Pooper (RP) and Dion–Jacobson (DJ) perovskites, 2D/3D heterostructures, TiO 2 bulk, and two-dimensional materials like black phosphorus, boron nitride, and others. 23,33–37 Earlier photo-induced charge dynamics experiments on 2D DJ perovskites, 2D RP perovskites with edge states and varying numbers of layers, and MAPbI 3 with grain boundaries and localized charges and interfaced with NiO, TiO 2 , and water yielded good findings. 11,33,34,38…”
mentioning
confidence: 98%
“…15,53,54 Therefore, it is of the utmost importance to maintain the photogenerated electrons (e) and holes (h) at their places at the band edges for an extended period of time. 29,37,54–56 In order to accomplish this, it is essential that holes be concentrated at the VBM level of the heterostructure, and that electrons reach the CBM level as rapidly as is physically possible by losing as much energy as they have. 57…”
mentioning
confidence: 99%
“…The photocarrier dynamics was exploited by NAMD simulation as implemented in the Hefei-NAMD code, where the nonadiabatic couplings were estimated using the CA-nonadiabatic coupling (NAC) module . The free energy diagram in the NRR process was obtained based on the concept of the computational hydrogen electrode model developed by Norskov et al The details of NAMD simulations can be found elsewhere, , and the NRR calculations are available in Supporting Information.…”
mentioning
confidence: 99%
“…2D stacked heterojunctions offer the highest degree of interface contact, facilitating interfacial charge transfer and separation, and thus, identifying suitable 2D materials for constructing g-C 3 N 4 -based Z-scheme photocatalytic systems with high performance is crucial. , Hexagonal boron nitride (h-BN) nanosheets, another metal-free 2D material structurally similar to graphene, have garnered extensive attention due to their excellent photocatalytic properties, including large surface area, high thermodynamic stability, and good thermal conductivity . However, as pointed out by Xu et al, the relatively large band gap of h-BN (4–6 eV) puts severe limitations on its photocatalytic applications under visible light response.…”
mentioning
confidence: 99%
“…The two important parameters, namely, nonadiabatic coupling (NAC) and pure dephasing time, which one obtains from the NAMD simulation, practically determine the requisite time frame for photogenerated charge carrier separation, interfacial transfer, and carrier recombination. More precisely, NAC quantifies inelastic charge–phonon scattering, responsible for electron–phonon energy transfer, while the pure-dephasing time governs the coherence loss between the involved states of SC1 and SC2. ,, The average NAC matrix element ( d ij ) between two states i and j is defined by boldd italici italicj = φ i true| t true| φ j = false⟨ φ i | R | φ j false⟩ ϵ j ϵ i ( R t ) where Ĥ is the Kohn–Sham Hamiltonian, ε i / j is the energy of the electronic state φ i / j as a function of time, and bold-italicR t determines the nuclear velocity. In general, higher NAC values signify faster electron and hole relaxation times.…”
mentioning
confidence: 99%